INTEGRATION OF GNSS AND LASER SCANNING FOR IMPROVING THE ACCURACY OF LARGE-SCALE GEODETIC MAPS: INTEGRATION OF GNSS AND LASER SCANNING FOR IMPROVING THE ACCURACY OF LARGE-SCALE GEODETIC MAPS - Yankova, Nigyar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This paper examines the integration of Global Navigation Satellite Systems (GNSS) and Terrestrial Laser Scanning (TLS) as an effective approach to enhance both the accuracy and spatial detail of geodetic measurements. The principles of each technology are presented, along with the advantages of their combined application in georeferencing, 3D modeling, and large-scale mapping.